Expert opinion on pre and post procedure care in aesthetic dermatology - Madnani, Nina; Vedmurthy, Maya; Parthasarthi, Anchala; Dhawan, Sachin; Kandhari, Rajat; Pillai, Rahul; Nischal, K. C. (International Journal of Research in Medical Sciences, 2022)
In clinical practice, the number of aesthetic dermatology procedures carried out in India is increasing. Nonsurgical or minimally invasive cosmetic dermatology encompasses a variety of procedures, such as chemical peels, laser therapies, dermal fillers, derma rollers and microneedling radiofrequency, which are known to be safe and effective. Despite enormous advances in the field of aesthetic dermatological procedures, many clinicians seem to have limited knowledge about the potential benefits and risks associated with aesthetic procedures. To ensure successful outcome of an aesthetic procedure and to minimise complications, one should be aware of the pre- and post-procedural care involved. This review summarized expert opinion on pre and post-procedural care needed with chemical peels, laser therapies, dermal fillers, derma rollers and microneedling radiofrequency.